Potret Manajemen Model Sekolah di SMA Athirah Boarding School Bukit Baruga Makassar: Portrait of School Model Management at SMA Athirah Boarding School Bukit Baruga Makassar - Reza Ramadani; Ely Syamdhitatia; Ahlun Ansar; Arismunandar; Yudhi Herawan (Pendidikan Al-Gafari, 2025)
This study discusses the portrait of school model management at SMA Athirah Islamic Boarding School Bukit Baruga Makassar, focusing on the Management Model, Excellent Programs, and Curriculum. The purpose of this study is to analyze and describe the management model applied at SMA Athirah Islamic Boarding School Bukit Baruga Makassar. The method used is qualitative, collecting data through interviews, observations, and documentation. The study results indicate that SMA Athirah has excellent programs such as entrepreneurship classes and student final projects that support the development of student creativity. In addition, a clear organizational structure and support from experienced educators contribute to the success of learning management. In conclusion, SMA Athirah Islamic Boarding School has succeeded in implementing a well-integrated curriculum, providing a quality educational experience, and shaping students' characters in accordance with Islamic values. This study is expected to be a reference for the development of other boarding schools in Indonesia.